Mammary gland cancer - Aguiar, Alberto; Musé, Miguel; D'Auria, Agustín; Leborgne, Félix; Musé, Miguel; Priario, Julio C; Estrugo, Roberto; Wilks, Arturo; Maggiolo, Jorge; Sabini, Graciela; et al. (Cirugía del Uruguay, 1984)
Panel discussions clearly indicate that the anamnesis and examination are valuable elements for the diagnosis of mammary gland canear, evaluating its diagnostic efficiency in a 94%. The diagnostic is confirmad by the severa! complementary examinations requested as per a defined algorhythm, according to the clínica! stage obtained as per T.N.M. classification